MtPT5 phosphate transporter is involved in leaf growth and phosphate accumulation of Medicago truncatula - Wang, Xue; Wei, Chunxue; He, Fei; Yang, Qingchuan (Frontiers in Plant Science, 2022)
Phosphorus (P) is an indispensable mineral nutrient for plant growth and agricultural production. Plants acquire and redistribute inorganic phosphate (Pi) via Pi transporters (PHT1s/PTs). However, apart from MtPT4, functions of the M. truncatula (Medicago truncatula) PHT1s remain unclear. In this study, we evaluated the function of the PHT1 family transporter MtPT5 in M. truncatula. MtPT5 was closely related to AtPHT1; 1 in Arabidopsis (Arabidopsis thaliana) and GmPT7 in soybean (Glycine max). MtPT5 was highly expressed in leaves in addition to roots and nodules. Ectopic expression of MtPT5 complemented the Pi-uptake deficiency of Arabidopsis pht1;1Δ4Δ double mutant, demonstrating the Pi-transport activity of MtPT5 in plants. When overexpressing MtPT5 in M. truncatula, the transgenic plants showed larger leaves, accompanying with higher biomass and Pi enrichment compared with wild type. All these data demonstrate that MtPT5 is important for leaf growth and Pi accumulation of M. truncatula and provides a target for molecular breeding to improve forage productivity.